Financial education through the lens of the EduFin framework: comparing two pedagogies in primary education - Andreatti, Giovanna; Morselli, Daniele; Parricchi, Monica (Frontiers in Education, 2025)
IntroductionFinancial literacy is increasingly recognized as essential for personal and societal well-being, yet its effective integration in primary education remains underexplored. This study examines the application of the European EduFin Framework in evaluating two financial education programs—one based on cooperative learning, the other on game-based learning—in an Italian primary school.MethodsEmploying a case study design, two fifth-grade classes participated in tailored financial education modules. Each session concluded with focus groups, and pupils’ reflections were subjected to qualitative content analysis. Learning outcomes were mapped against the EduFin Framework using convergence and divergence matrices to assess alignment with targeted competences.ResultsBoth pedagogical approaches primarily addressed the “Money and Transactions” domain of the EduFin Framework, with limited coverage of “Risk and Reward.” While the framework facilitated systematic evaluation and comparison of program content, findings indicate it emphasizes knowledge transmission over broader competence development, particularly regarding social and collaborative skills.DiscussionThe EduFin Framework offers valuable structure for assessing financial education initiatives but may constrain holistic competence development due to its individualistic focus. However, integrating active, student-centered pedagogies—such as cooperative and game-based learning—can help foster social skills and deeper learning, partially overcoming these limitations.ConclusionThe study highlights both the utility and constraints of the EduFin Framework in primary education, underscoring the need for pedagogical approaches that balance content mastery with competence and social skill development.